analysis of the characteristics of groundwater in the Tulul Al-Tar area - Judeh, Hussein Ghazi; Jabir, Ahmed Abdul Sattar (Al-Adab Journal, 2022)
Groundwater is one of the important water sources in arid and semi-arid regions. However, it is the main source the water used for human, industrial and irrigation purposes. Thus, its pollution by industrial and human activities requires serious attention, especially in areas that lack the presence of surface water. This study he (analysis of the characteristics of groundwater in the Tulul Al-Tar area) addresses the problem of water scarcity in the region through making use of groundwater. The study will be presented to the relevant authorities represented by (the General Authority for Groundwater). The boundaries of the study area are bordered by the Euphrates River from the east and Anbar Governorate From the west, Karbala Governorate and the southern coasts of Lake Al-Razzaza from the north, and Najaf Governorate from the south. The study area is characterized by the variation of groundwater levels, which requires us to study its quantities and trends of change in characteristics and causes. This was done through the analysis of its levels, collection of laboratory samples and study of its physical and chemical properties. The study used the Gibbs diagram (1970, Gibbs) to find out the hydrogeochemical phenomena of groundwater and the mechanism that controls the chemical composition of groundwater. The chemical analysis of wells showed a high degree of acidity. Additionally, through the use of a compression scheme, it was found that the same concentration falls within the rule of rocks. Finally, the presence of wells suitable for human and agricultural activities was also discovered.